SYNTHESIS OF MODULAR-STRUCTURED SYSTEMS FOR AUTOMATIZATION OF DECISION-MAKING PROCESSES IN TRANSPORT LOGISTICS - Kondratenko, Yuriy; Encheva, Sylvia; Sidenko, Ievgen (International Journal of Computing, 2014)
The ranging analysis of transport logistics problems and decision-making methods were held in the paper. The problems, which are represented as subsystems of DSS (Decision Support System) module type, were considered. One of which, in particular, evaluation of the quality of transport services to select cargo shipping company, was considered in details.